C-band tunable performance of passively Q-switched erbium-doped fiber laser using Tin(IV) oxide as a saturable absorber - Siddiq, Nur Abdillah; Chong, Wu Yi; Pramono, Yono Hadi; Muntini, Melania Suweni; Ahmad, Harith (Elsevier, 2019)
We report on the detailed study of wavelength tunability of passively Q-switched erbium doped fiber laser using Tin(IV) Oxide (SnO 2 ) as saturable absorber (SA). As a typical n-type semiconductor, SnO 2 has been widely used in gas sensors, oxidation catalyst, transparent conductor, and electrode materials in solar cell. Herein, we fabricated saturable absorber by compositing SnO 2 nanoparticle with polyvinyl alcohol (PVA). The SnO 2 -SA is incorporated in the laser cavity by sandwiching it between two fiber ferrules. Q-switched laser operation can be continuously tuned from 1521 to 1565 nm, with a wavelength tuning range of up to 45 nm, covering almost the entire C-band. Q-switched pulse parameters such as repetition rate, average power, pulse width, pulse energy, and peak power at different wavelengths were studied in detail. Our experimental results suggest that the SnO 2 -SA is a suitable and cost-effective solution for broadband tunable laser applications with relatively simple fabrication process. © 2019 Elsevier B.V.